2020
DOI: 10.1016/j.surfcoat.2020.126319
|View full text |Cite
|
Sign up to set email alerts
|

Probing fatigue resistance in multi-layer DLC coatings by micro- and nano-impact: Correlation to erosion tests

Abstract: DLC coatings have seen recent use as protective coatings for flow control devices in the oil and gas industries. Improving fatigue resistance for multi-layered DLC coatings on hardened steel is key for improving their performance in this harsh environment of highly loads repetitive contact. This has been studied directly by micro-scale repetitive impact tests at significantly higher strain rate and energy than in the nano-impact test, enabling the study of coating fatigue with spherical indenters and dry erosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 90 publications
1
4
0
Order By: Relevance
“…This was confirmed by nanoindentation tests to ~25-30% of the total coating thickness that revealed little change in hardness from tests at much lower depth. Although the hardened substrate improved impact resistance somewhat, there was cracking after a few impacts on a-C:H and Si-a-C:H. The SEM images in figures 7-8 show delamination, consistent with cracking starting at or near the interfaces, as was observed in the studies above, in FIB sections of impact craters on Si-a-C:H [79] and on graded a-C:H under similar test conditions [39].…”
Section: Impactsupporting
confidence: 73%
See 1 more Smart Citation
“…This was confirmed by nanoindentation tests to ~25-30% of the total coating thickness that revealed little change in hardness from tests at much lower depth. Although the hardened substrate improved impact resistance somewhat, there was cracking after a few impacts on a-C:H and Si-a-C:H. The SEM images in figures 7-8 show delamination, consistent with cracking starting at or near the interfaces, as was observed in the studies above, in FIB sections of impact craters on Si-a-C:H [79] and on graded a-C:H under similar test conditions [39].…”
Section: Impactsupporting
confidence: 73%
“…show that there was cohesive cracking for a-C:H:W deposited without a CrN sublayer but again interfacial delamination was not observed [79]. Ramirez and co-workers reported enhanced resistance to contact fatigue for W-doped DLC with ~7.5 GPa hardness on hardened tool steel [35].…”
Section: Impactmentioning
confidence: 96%
“…Although the model has not been validated under cyclic conditions, several experimental studies with sharper and blunter probe geometries [10][11][12][37][38][39][40] have shown that hard PVD coatings can display a level of fatigue behaviour under cyclic loading. In addition to the coating mechanical properties, the type of cracking observed depends on a range of factors including probe geometry, coating thickness, severity of loading and number of cycles.…”
Section: Experimental Evidence For Coating Fatigue Behaviour Under Cy...mentioning
confidence: 99%
“…The location of the crack at the top surface at the periphery of the contact predicted by the model has also been seen in experimental studies of repetitive micro-scale impact by spherical indenters with smaller end radii (17-20 µm). For example, Beake, Liskiewicz and co-workers used the recently developed micro-impact technique to investigate the micro-scale impact resistance of hard carbon coatings on hardened tool steel [10,12,37] and PVD nitrides on cemented carbide [11,12,38].…”
Section: Experimental Evidence For Coating Fatigue Behaviour Under Cy...mentioning
confidence: 99%
“…The former can provide much closer simulation of actual service environment of materials under highly loaded intermittent contact by performing repetitive impact at a particular location, and evaluate the behavior of impact wear, adhesive failure and fatigue fracture qualitatively by recoding the evolution of impact depth-time curves in real time (Fig. 1b) [16][17][18]. In general, a single rapid increase in penetration depth may represent the adhesive failure of the coatings, and a series of several smaller jumps in the penetration depths corresponds to a more gradual cohesive failure.…”
Section: Introductionmentioning
confidence: 99%